2012
DOI: 10.1002/jso.23105
|View full text |Cite
|
Sign up to set email alerts
|

Irregular osteotomy in limb salvage for juxta‐articular osteosarcoma under computer‐assisted navigation

Abstract: With careful patient selection, the irregular osteotomy under navigation guidance was proved to be an effective and safe technique for precise tumor resection in joint preserving limb salvage procedures for treating patients with juxta-articular osteosarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Although histological examinations of all specimens showed a clear tumor margin in all patients like in previous reports [8,10,14,17,20,21] with this technique, it is important to note that the navigation assistance only reproduces accurately the preoperative plan performed by the surgeon based on fusion images (CT and MRI). However, the surgeon could misinterpret those preoperative images and plan inadequate cuts that could lead to inadequate margins.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Although histological examinations of all specimens showed a clear tumor margin in all patients like in previous reports [8,10,14,17,20,21] with this technique, it is important to note that the navigation assistance only reproduces accurately the preoperative plan performed by the surgeon based on fusion images (CT and MRI). However, the surgeon could misinterpret those preoperative images and plan inadequate cuts that could lead to inadequate margins.…”
Section: Discussionsupporting
confidence: 51%
“…In orthopaedic oncology, this technology is reported to aid in achieving adequate margins [8,20] and improve the accuracy of bone cuts [10,14,21]. However, it will likely become more extensively used if it decreases the time of the procedures and shows that clinical outcomes are improved [4,16]; to date, these remain open questions.…”
Section: Introductionmentioning
confidence: 99%
“…The use of computer-assisted navigation technologies might help surgeons perform more accurate resections [2,11,15]. However, some papers have reported problems related to the use of navigation, including increased operative time as a result of the additional technological complexity; in addition, there is no evidence of which we are aware suggesting that navigation decreases the risk of local recurrence [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…This surgical assistance is becoming more frequently used in limb salvage surgery to preserve as much host tissue as possible without compromising tumor margins and may help surgeons perform more accurate resections [11,15,16,18]. However, previous reports about navigation in trauma and arthroplasty have suggested that computer assistance techniques do not improve patient-reported outcomes and that these techniques add surgical time [6,8,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…We used the navigation method described by Li et al [19]. CT images of the lesion with slices of 0.625 mm and MR images with slices of 2 mm were obtained.…”
Section: Surgical Proceduresmentioning
confidence: 99%